Bifurcation Analysis of a Synthetic Drug Transmission Model with Two Time Delays - Hu Zhang; Anwar Zeb; Aying Wan; Zizhen Zhang (Mathematics, 2022)
Synthetic drugs are taking the place of traditional drugs and have made headlines giving rise to serious social issues in many countries. In this work, a synthetic drug transmission model incorporating psychological addicts with two time delays is being developed. Local stability and exhibition of Hopf bifurcation are established analytically and numerically by taking the combinations of the two time delays as bifurcation parameters. The exhibition of Hopf bifurcation shows that it is burdensome to eradicate the synthetic drugs transmission in the population.